Комунікативні інтенції сучасних прозових текстів у підручниках з української мови - Хоменко, О.; Галактіонова, Н. (Культура слова, 2019)
У статті проаналізовано чотири сучасні підручники з української мови, досліджено способи розгортання дискурсивності сучасної української прози в практиці підручникотворення. Подано рекомендований перелік авторів, яких було б доречно використовувати в сучасному підручнику. Продемонстровано як комунікативні рівні концептуалізації сучасної прози безпосередньо поєднуються із соціокультурними парадигмами мовотворення. The semiotic-word-forming practices of national writing as one of the most defining forms of expression of the spiritual creativity of Ukrainians have been recognized in the discursive space of Ukrainian language textbooks. In our research, we have demonstrated how contemporary Ukrainian prose unfolds its discursiveness in the space of textbooksʼ creation that is relevant today, textbooksʼ creation which is «here – and – now» presenting in the practice of modern Ukrainian schools. In our article, first of all we have indicated what names contemporary Ukrainian prose represents in current textbooks of Ukrainian language (different collectives), we have shown that in the process of studying Ukrainian language prose remains one of the main sources of emotional influence on the student. Having analyzed four school textbooks, we have come to the conclusion that the communicative levels of conceptualization of contemporary prose in contemporary textbooks of the Ukrainian language directly correspond to socio-cultural paradigms of linguistics as a factor of the historical, cultural and social being of the Ukrainian people. Representing contemporary prose, the authors of the textbooks represent a whole new wave of Ukrainian cultural revival, realized to the greatest extent in writing.